Neutrophil extracellular traps in tumor progression and immunotherapy - Yan, Meina; Gu, Yifeng; Sun, Hongxia; Ge, Qinghong (Frontiers in Immunology, 2023)
Tumor immunity is a growing field of research that involves immune cells within the tumor microenvironment. Neutrophil extracellular traps (NETs) are neutrophil-derived extracellular web-like chromatin structures that are composed of histones and granule proteins. Initially discovered as the predominant host defense against pathogens, NETs have attracted increasing attention due to they have also been tightly associated with tumor. Excessive NET formation has been linked to increased tumor growth, metastasis, and drug resistance. Moreover, through direct and/or indirect effects on immune cells, an abnormal increase in NETs benefits immune exclusion and inhibits T-cell mediated antitumor immune responses. In this review, we summarize the recent but rapid progress in understanding the pivotal roles of NETs in tumor and anti-tumor immunity, highlighting the most relevant challenges in the field. We believe that NETs may be a promising therapeutic target for tumor immunotherapy.